Quality of Growth Empirics: Comparative Gaps, Benchmarking and Policy Syndromes - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
This study uses a new dataset to provide comparative gaps, benchmarking with best performers and policy syndromes of growth quality in 93 developing countries with data for the period 1990-2011. Sigma and Beta estimation strategies are used to provide between and within cross-country dispersions. The empirical evidence is based on: time, regions, income levels, resource-wealth, state fragility and time-consistent growth quality (GQ) performance. First, for `within dispersions' the following outcomes are established: (1) GQ dispersions within fundamental characteristics have been decreasing over time, (2) From a time-dynamic view, countries within Asia and the Pacific have experienced the highest reduction in GQ differences while nations in the Middle East and North Africa (Central and Eastern European) region have witnessed the highest (lowest) differences, (3) From an income perspective, upper-middle-income (Low-income) countries have the lowest (highest) differences in GQ. (4) Resource-rich and Non-fragile countries have higher differences relative to their Resource-poor and Fragile counterparts respectively. Second, for `between dispersions' and policy syndromes, we found two time-consistent extremities. (1) In decreasing need of policy intervention, the following are apparent for the Policy syndrome extreme: Hopeful, Fragile, Sub-Saharan African, Low-income and Resource-rich countries. (2) In the same line of policy inference, the following are apparent for the Syndrome-free extreme: Central and Eastern European, Asia and the Pacific, Latin American, Best Performing and Upper-middle-income countries. Their predispositions are clarified and policy implications discussed.
Keywords: O40; O57; I10; I20; I32; 330; Quality of growth; Development; Catch-up